Agrarian women, the gender of dairy work, and the two-breadwinner model in the Swedish welfare state - Sommestad, Lena, author.
1 online resource
Keywords: "In this volume, Lena Sommestad explores the significance of rural womanhood in the formation of Sweden's gender-egalitarian welfare state in the early 20th century. Drawing on a rich array of documents, photographs, and interviews with women and men, she analyzes the changing gender division of labor in dairying and illuminates the dynamic processes and debates that shaped industrial workplaces. The book demonstrates the importance of rural women's gainful labor and organized activism to Sweden's citizenship-based social policies, which enabled married women to combine childrearing with breadwinning"--